2007
DOI: 10.1016/j.neulet.2007.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auditory noise on the psychophysical detection of visual signals: Cross-modal stochastic resonance

Abstract: Harper [D.W. Harper, Signal detection analysis of effect of white noise intensity on sensitivity to visual flicker, Percept. Mot. Skills 48 (1979) 791-798] demonstrated that the visual flicker sensitivity was an inverted U-like function of the intensity of different levels of auditory noise from 50 to 90dB (SPL), without concomitant changes in the response bias. The aim of the present study was to extend these observations in the context of the stochastic resonance, a counterintuitive phenomenon in which a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
87
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 31 publications
16
87
0
2
Order By: Relevance
“…In a general context our study also supports previous findings about psychophysical multisensory SR in other sensory modalities (Lugo et al 2008a;Manjarrez et al 2007). For example, Lugo et al (2008a) demonstrated that auditory noise facilitates tactile, visual, and proprioceptive sensations via cross-modal SR, showing that this phenomenon is a ubiquitous property in psychophysical experiments in humans.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In a general context our study also supports previous findings about psychophysical multisensory SR in other sensory modalities (Lugo et al 2008a;Manjarrez et al 2007). For example, Lugo et al (2008a) demonstrated that auditory noise facilitates tactile, visual, and proprioceptive sensations via cross-modal SR, showing that this phenomenon is a ubiquitous property in psychophysical experiments in humans.…”
supporting
confidence: 91%
“…Specifically, Harper reported the inverted U-like increase in the sensitivity to visual flicker produced by the addition of auditory white noise (Harper 1979). Similar psychophysical results with an inverted U-like increase were reported by our research group when we employed auditory noise and the application of subthreshold visual stimuli with a pair of LEDs (Manjarrez et al 2007), and we then employed for the first time the term "cross-modal stochastic resonance." Later, Lugo et al (2008a) examined the psychophysical effects of auditory noise in other sensory modalities, thus confirming the observation of crossmodal stochastic resonance.…”
Section: Comparison With Earlier Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…These reports motivated the analysis of SR on tactile evoked potentials in humans and cats (Manjarrez et al, 2002a(Manjarrez et al, ,b, 2003. SR effects were shown not only in the somatosensory, but also in visual and auditory systems (Simonotto et al, 1997;Jaramillo and Wiesenfeld, 1998;Volgushev and Eysel, 2000;Manjarrez et al, 2007;Aihara et al, 2010). In the motor system, Fallon et al (2004) demonstrated that broadband (0 -300 Hz) noise improved the afferents sensitivity from Golgi tendon organs, primary and secondary muscle spindles in cat, in line with an earlier study on humans muscle spindle receptors (Cordo et al, 1996).…”
Section: Introductionsupporting
confidence: 73%